2009
DOI: 10.5194/acp-9-8377-2009
|View full text |Cite
|
Sign up to set email alerts
|

NO<sub>x</sub> production by lightning in Hector: first airborne measurements during SCOUT-O3/ACTIVE

Abstract: Abstract. During the SCOUT-O3/ACTIVE field phase in November–December 2005, airborne in situ measurements were performed inside and in the vicinity of thunderstorms over northern Australia with several research aircraft (German Falcon, Russian M55 Geophysica, and British Dornier-228. Here a case study from 19 November is presented in detail on the basis of airborne trace gas measurements (NO, NOy, CO, O3) and stroke measurements from the German LIghtning Location NETwork (LINET), set up in the vicinity of Darw… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
71
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 46 publications
(79 citation statements)
references
References 112 publications
4
71
2
Order By: Relevance
“…Unlike the Brazilian (Huntrieser et al, 2008) and Australian (Huntrieser et al, 2009) thunderstorms, the AMMA MCSs showed a greater influence from boundary layer versus lightning NO x . The tropical and subtropical MCSs investigated during AMMA indicated LNO x production rates (70 moles flash −1 and 179 moles flash −1 , respectively) were comparable to those observed in similar air mass thunderstorms during TROCCINOX.…”
Section: Lno X Production In Tropical Thunderstormsmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike the Brazilian (Huntrieser et al, 2008) and Australian (Huntrieser et al, 2009) thunderstorms, the AMMA MCSs showed a greater influence from boundary layer versus lightning NO x . The tropical and subtropical MCSs investigated during AMMA indicated LNO x production rates (70 moles flash −1 and 179 moles flash −1 , respectively) were comparable to those observed in similar air mass thunderstorms during TROCCINOX.…”
Section: Lno X Production In Tropical Thunderstormsmentioning
confidence: 99%
“…Based on the Tropical Convection, Cirrus, and Nitrogen Oxides Experiment (TROCCINOX) in Brazil, the LNO x mass production for tropical thunderstorms was of similar magnitude as that found for one of the BIBLE-C storms (∼ 70 moles flash −1 ), while a subtropical thunderstorm also analyzed during the campaign had a production rate of ∼ 140-210 moles flash −1 (Huntrieser et al, 2008). Huntrieser et al (2009) (Labrador et al, 2009), while later in the ACTIVE experiment (e.g., January 2006) enhancements in LNO x were found over widespread regions.…”
Section: Lno X Production In Tropical Thunderstormsmentioning
confidence: 99%
“…But at least most events with low P are indeed tropical events, which might thus be less productive due to low wind shears. Huntrieser et al (2009) also proposed that warm rain processes, which might be dominant for the tropical morningtime thunderstorms of this study, may result in very short flash components. I.e., though the detected events show -by selection -high FRD, these flashes might generally be less productive in producing NO x compared to flashes for mixedphase precipitation processes with probably longer flash channels.…”
Section: Factors Determining Pementioning
confidence: 99%
“…They propose that tropical thunderstorms have generally shorter flash lengths, and are thus generally less productive with respect to LNO x /flash, than subtropical thunderstorms, as a consequence of enhanced vertical wind shear of the latter. In Huntrieser et al (2009) correlations of P with vertical wind shear are reported using in-situ measurements from the TROCCINOX and SCOUT-O 3 campaigns.…”
Section: Factors Determining Pementioning
confidence: 99%
See 1 more Smart Citation